The Newer Horizons in Bariatric Surgery - Mushtaq Chalkoo (Archives of Clinical Gastroenterology - Peertechz Publications, 2017)
Weight is one of the very important parameters of good health. Obesity is now a recognized disease, considered to be a global epidemic. It is increasing in prevalence in adults, adolescents and children. A low level of physical activity, increased use of energy rich, and nutrient poor foods with high levels of sugar and saturated fat has led to increased rates of obesity in different areas like America, United  Kingdom, Europe and the Middle East. The prevalence of obesity among adults rose from 14.9% to 24.9% between 1993 and 2013. The cost of obesity and its commorbities have upsurged to three billion Euros per year. It is predicted that by 2050; 60% of adult men, 50% of adult women and 25 percent of children will be engulfed by this disease of obesity. It is beyond doubt to express that morbidly obese people have high risk of physical and metabolic commorbities that impair their health and increase motartility.